Spo0A links de novo fatty acid synthesis to sporulation and biofilm development in Bacillus subtilis - Pedrido, María Eugenia (2012)
During sporulation in Bacillus subtilis, the committedcell undergoes substantial membrane rearrangements to generate two cells of different sizes and fates: the mother cell and the forespore. Here, we demonstrate that the master transcription factor Spo0A reactivates lipid synthesis during development. Maximal Spo0Adependent lipid synthesis occurs during the key stages of asymmetric division and forespore engulfment. Spo0A reactivates the accDA operon that encodes the carboxylase component of the acetylCoA carboxylase enzyme, which catalyses the first and rate-limiting step in de novo lipid biosynthesis, malonyl-CoA formation. The disruption of the Spo0Abinding box in the promoter region of accDA impairs its transcriptional reactivation and blocks lipid synthesis. The Spo0A-insensitive accDA0A cells were profi- cient in planktonic growth but defective in sporulation (sE activation) and biofilm development (cell cluster formation and water repellency). Exogenous fatty acid supplementation to accDA0A cells overcomes their inability to synthesize lipids during development and restores sporulation and biofilm proficiencies. The transient exclusion of the lipid synthesis regulon from the forespore and the known compartmentalization of Spo0A and ACP in the mother cell suggest that de novo lipid synthesis is confined to the mother cell. The significance of the Spo0A-controlled de novo lipid synthesis during B. subtilis development is discussed.